The Effects of Vocabulary and Grammar Mastery on Students' Writing Skill - Lilik Yuliawati (Universitas Majalengka, 2021)
Writing is not just production of text. It is also process of learning and trying out the ideas to choose the proper words with correct grammatical rules. The objective of the research is to know the effects of vocabulary and grammar mastery on students’ writing skill. This research used survey method with total sample of the research is 40 students. The data were collected by giving three sets of objective test as the instruments to the 40 students. The data analysis technique of the research is multiple linear regression analysis. The research findings show: 1) There is a significant effect of vocabulary and grammar mastery simultaneously on students’ writing skill. 2) There is a significant effect of vocabulary mastery on students’ writing skill.. 3) There is a significant effect of grammar mastery on students’ writing skill.